Analisis Strategi Peningkatan Kualitas Sumber Daya Manusia Melalui Implementasi Indikator KPI Pada Divisi Operasional PT. Bank OCBCNISP Tbk - Tri Surya; Hadi Supratikta; Agustina Mogi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research is titled Analysis of Strategies to Improve Human Resource Quality Through the Implementation of KPI Indicators in the Operational Division of PT. Bank OCBCNISP Tbk. The purpose of this study is to understand the phenomenon and obtain empirical evidence, as well as conclusions about the strategies carried out by PT. Bank OCBCNISP Tbk and their effectiveness. This type of research is a document study, descriptive qualitative in nature, because this research seeks to analyze and interpret based on written documents. Data collection techniques include interviews and documentation. The interview technique used is unstructured interviews. Interviews were conducted with 5 managers and 5 operational employees. Data analysis was carried out using the BCG Matrix model to map the position of KPI indicators based on two dimensions, namely, the level of contribution to operational performance and the level of implementation difficulty. The results of this study show that KPI indicators can be classified into four quadrants: (1) Stars, Defect / Human Error KPI, Fulfillment of SLA, and No Operational Loss, have high contributions and are easy to implement, so they need to be maintained and improved. (2) Question Marks, Continuous Improvement / Process Simplification KPI and Agile Operation / Multitasking Implementation, have high contributions but are difficult to implement. (3) Cash Cows, Profit after Tax and OPEX below budget / Efficiency KPI, have stable contributions and are easy to implement. (4) Dogs, Internal Customer Survey, Productivity, Training, New Activity, Competencies, and Value KPI, have stable contributions and tend not to significantly impact evaluations. Keywords: Strategy, HR Quality, Key Performance Indicator